A rare case of ruptured caesarean scar pregnancy - Bhatia, Pooja; Gupta, Radhika; Kaur, Manjeet; Pandher, Dilpreet K.; Tandon, Rimpy; Goel, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Caesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy. The incidence is approximately 1:2000 pregnancies and has potentially life-threatening complications. Ours is a rare case of scar ectopic pregnancy who had taken medical termination of pregnancy (MTP) kit while being unaware of her pregnancy location and presented with uterine rupture and hemoperitoneum. A 24-year-old female, P2L2A1, with previous two caesarean section (CS), presented with the complaint of bleeding per vaginum with acute pain abdomen and history of MTP kit intake at 7 weeks’ period of gestation (POG). She received symptomatic treatment at local hospital without any diagnosis being made but brought an ultrasound showing anterior myometrium defect with scar site hematoma and free fluid. She presented with moderate pallor, tachycardia and suprapubic tenderness. She was subsequently taken up for laparotomy in view of probable ruptured CSP. Intra-operatively, actively bleeding scar ectopic was seen with hemoperitoneum. The contents were scooped out and repair done with bilateral tubal ligation. She was resuscitated with adequate blood products. Embryo implantation in the region of a previous CS scar is rare and a delay in either diagnosis or treatment can have catastrophic complications like haemorrhage, rupture and significant maternal morbidity as seen in our case. Therefore, we should have a high index of suspicion of scar pregnancy especially in cases of previous CS so that timely intervention can be done preventing maternal morbidity. Unwarranted use of misoprostol can be deleterious when site of implantation is unknown, particularly in CSP.